Factors influencing customer satisfaction towards Unifi service in Malaysia - Fofana, Youssouf (Kulliyyah of Economics and Management Science, International Islamic University Malaysia, 2020)
Customer satisfaction is the most important determinant of service provider sectors. These service companies are concerning about customer needs and expectations. Many of these service companies have provided and implemented customer satisfaction strategy as premier operational goal. And also they are concern finding factors that influence customer satisfaction in order to extend their business. The performance of any business existence depends on the growth in which customers have been satisfied. The increase of telecommunication industry in Malaysia explains clear signs of a consistently in network technologies and high demand of customer for high-speed data communication. Service provider companies are attempting to attract more customers and thus cause a competitive environment. For service provider companies to sustain in the competitive market economy, the need to centralize customers in their customer satisfaction strategy. The main objective of this study aimed to investigate the factors influencing customer satisfaction towards Unifi service in Malaysia. The study explored the different element that affect Unifi customer satisfaction and increase fulfillment of their needs and expectations. The study investigates three factors that influence customer satisfaction towards Unifi service in Malaysia which are network quality, billing/price and brand image. A self-questionnaire was adopted to give out 20 questions items to 200 respondents within Klang Valley area and online networking sites in Malaysia. The collected data was analyzed by employing Statistical Package for the Social Sciences (SPSS) software. The internal consistency reliability test of Cronbach's alpha demonstrated that all scale of items was been proved reliable. Multiple regression was used to investigates the relationship between independent variables and the dependent variable. The results have proven a significant relationship among the two independent variables, that are brand image and billing/price with dependent variable which is customer satisfaction. Brand image is the most influential and important factor customer satisfaction towards Unifi service in Malaysia. Whereas the network quality has given no significant relationship with customer satisfaction. The findings of this study have implications and recommendations for Unifi service, as it has provided a detailed and thorough understanding of Unifi service subscribers by considering network quality. The study also offered the Unifi service a suggestion of their network quality for better and high customer satisfaction in developing new strategies.